2016
DOI: 10.1016/j.imlet.2016.07.010
|View full text |Cite|
|
Sign up to set email alerts
|

Development of a flow cytometry-based potency assay for measuring the in vitro immunomodulatory properties of mesenchymal stromal cells

Abstract: Rhodri. (2016). Development of a flow cytometry-based potency assay for measuring the in vitro immunomodulatory properties of mesenchymal stromal cells. Immunology Letters, 177,[38][39][40][41][42][43][44][45][46] We conclude that this protocol represents a practical, quantitative assay of a clinically relevant functional effect of hBM-MSCs as well as other immunomodulatory agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…It has been shown that MSCs from donors with a high proliferation rate are smaller in size, have longer telomeres and show enhanced ectopic bone forming capacity compared with MSCs from donors with a lower proliferation rate . For other therapeutic applications, different sets of potency tests may be required, such as proposed for the selection of MSC donors with above average immunomodulatory capacity . At the moment, relevant in vitro potency tests that enable selection of MSC donors and batches with enhanced therapeutic efficacy are very limited.…”
Section: Mechanism Of Action; Current State Of the Artmentioning
confidence: 99%
“…It has been shown that MSCs from donors with a high proliferation rate are smaller in size, have longer telomeres and show enhanced ectopic bone forming capacity compared with MSCs from donors with a lower proliferation rate . For other therapeutic applications, different sets of potency tests may be required, such as proposed for the selection of MSC donors with above average immunomodulatory capacity . At the moment, relevant in vitro potency tests that enable selection of MSC donors and batches with enhanced therapeutic efficacy are very limited.…”
Section: Mechanism Of Action; Current State Of the Artmentioning
confidence: 99%
“…Flow cytometry is also suitable to analyze cytokine expression in specific cells after intracellular immunostaining, which has already been used to investigate the influence of MSC on T cells [25, 29]. Furthermore, in a possibly trend-setting approach for estimating MSC potency, flow cytometry has been used to analyze MSC-mediated suppression of monocyte activation in whole blood, as determined via intracellular TNF-α staining [31].…”
Section: Introductionmentioning
confidence: 99%
“…Assays to assess the immunomodulation capacities of MSC include: Inhibition of mitogen/alloantigen‐induced T‐cell proliferation Suppression of CD154 activation marker expression on CD4 T cells CD200 expression as an indicator or surrogate marker for suppression (however, blocking did not impair suppressive strength) Inducible indoleamine 2,3‐dioxygenase 1 and programmed death ligand 1 expression TNF‐α expression in lipopolysaccharide‐stimulated macrophages MSC‐induced interleukin (IL)‐10 release from blood cells …”
Section: Quality Controlmentioning
confidence: 99%